Curcumin regulates pulmonary extracellular matrix remodeling and mitochondrial function to attenuate pulmonary fibrosis by regulating the miR-29a-3p/DNMT3A axis - Meng‐Hsuan Cheng; Hsuan‐Fu Kuo; Chia-Yuan Chang; Jui‐Chi Chang; I-Hshiang Liu; Chong‐Chao Hsieh; Chih‐Hsin Hsu; Chia‐Yang Li; Shu‐Chi Wang; Yung‐Hsiang Chen; Chuang‐Rung Chang; Tsung‐Ying Lee; et al. (2024)
Epigenetic regulation and mitochondrial dysfunction are essential to the progression of idiopathic pulmonary fibrosis (IPF). Curcumin (CCM) in inhibits the progression of pulmonary fibrosis by regulating the expression of specific miRNAs and pulmonary fibroblast mitochondrial function; however, the underlying mechanism is unclear. C57BL/6 mice were intratracheally injected with bleomycin (5 mg/kg) and treated with CCM (25 mg/kg body weight/3 times per week, intraperitoneal injection) for 28 days. Verhoeff–Van Gieson, Picro sirius red, and Masson's trichrome staining were used to examine the expression and distribution of collagen and elastic fibers in the lung tissue. Pulmonary fibrosis was determined using micro-computed tomography and transmission electron microscopy. Human pulmonary fibroblasts were transfected with miR-29a-3p, and RT-qPCR, immunostaining, and western blotting were performed to determine the expression of DNMT3A and extracellular matrix collagen-1 (COL1A1) and fibronectin-1 (FN1) levels. The expression of mitochondrial electron transport chain complex (MRC) and mitochondrial function were detected using western blotting and Seahorse XFp Technology. CCM in increased the expression of miR-29a-3p in the lung tissue and inhibited the DNMT3A to reduce the COL1A1 and FN1 levels leading to pulmonary extracellular matrix remodeling. In addition, CCM inhibited pulmonary fibroblasts MRC and mitochondrial function via the miR-29a-3p/DNMT3A pathway. CCM attenuates pulmonary fibrosis via the miR-29a-3p/DNMT3A axis to regulate extracellular matrix remodeling and mitochondrial function and may provide a new therapeutic intervention for preventing pulmonary fibrosis.